PROFESSION TRANSFER IN ISLAMIC PERSPECTIVE: LIFE CHANGES TOWARDS QODHO' AND QODHAR - Dwi Songgo Panggayudi (Ecopreneur.12, 2023)
The purpose of this study is to understand and reveal the behavior of employees at the shipping company PT. Meratus Line Surabaya, who are carrying out a profession transfer that is currently happening at PT. Meratus Line from an Islamic perspective. This research approach uses qualitative methods, using phenomenological approaches (Alfraed Schutz), religious phenomenology, conventional (Bogdan Biken) and IFIAS which see social behavior as behavior oriented towards the past, present and future of someone who changes professions. The results of this study indicate the behavior of seafarers at PT. Meratus Line Surabaya, namely: 1. Seafarers' brotherhood at PT. Meratus Line Surabaya is very strong, namely helping each other, for example for junior seafarers so that they can improve their competence quickly, 2. The seafarer profession has changed at PT. Meratus Line happens to senior sailors who have high competence to find their lost lives. 3. at PT. Meratus Line in an Islamic perspective as a result of being driven by feelings to seek happiness in life in accordance with Qodho' and human Qodhar, and 4. The shift of PT employees. Meratus Line, especially those who already have unique factors from their lives, both their life experiences, aspirations and the influence of social environmental factors where they live and work.Â